2003
DOI: 10.1107/s0907444903011491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mutations in the T1.5 loop of pectate lyase A fromErwinia chrysanthemiEC16

Abstract: Pectate lyase A (PelA) is a pectate-degrading enzyme secreted by plant pathogens. PelA from Erwinia chrysanthemi has 61% amino-acid identity and a conserved structural similarity to pectate lyase E (PelE). Although similar in structure and sequence, the enzymatic characteristics of PelA differ from those for PelE. A structural alignment of PelA and PelE reveals differences in the T1.5 loop. The sequence of the T1.5 loop in PelA was mutated to the homologous sequence in PelE. The crystal structure of the PelA T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This linkage creates an "accordion-like" conformation between neighboring residues due to its signature axial C-4 configuration. The overall fiber is extended and flexible and can adopt a 2 1 or 3 1 helix, depending on the degree of hydration and presence of cations (14,(21)(22)(23). Variation in the potential three-dimensional structure of pectic fibers was supported by the galacturonate pentasaccharide-Pel cocrystal structure, which revealed that the substrate was a mixture of both 2 1 and 3 2 helical conformations (59).…”
Section: Pectin Structurementioning
confidence: 94%
“…This linkage creates an "accordion-like" conformation between neighboring residues due to its signature axial C-4 configuration. The overall fiber is extended and flexible and can adopt a 2 1 or 3 1 helix, depending on the degree of hydration and presence of cations (14,(21)(22)(23). Variation in the potential three-dimensional structure of pectic fibers was supported by the galacturonate pentasaccharide-Pel cocrystal structure, which revealed that the substrate was a mixture of both 2 1 and 3 2 helical conformations (59).…”
Section: Pectin Structurementioning
confidence: 94%
“…S2, the supplementary note, and Table S3 in the supplemental material). Residue R236 is partially solvent exposed and is located in the T1.6 loop (the 6th loop of turn T1), which stacks against the T1.5 loop, containing a helical structure previously shown to enhance the catalytic activity of related pectate lyases (10). Its guanidinium The R236F substitution caused no structural change in the enzyme.…”
Section: Vol 74 2008 Thermostabilization Of Pectate Lyases 1185mentioning
confidence: 99%
“…Pels usually exist as multiple independently regulated isozymes that have 25-80% identity in amino acid sequence (Tamaki et al 1988;Hinton et al 1989). Comparison of the amino acid sequences of five major endo-Pels of E. chrysanthemi shows 60-84% identity (Bekri et al 1999;Dehdashti et al 2003). Shevchik et al (1997) cloned the pelI gene, of E. chrysanthemi 3937.…”
Section: Amino Acid Sequence Homologymentioning
confidence: 98%